Strengthening problem-solving competence of vocational high school students through a deep learning approach integrated with digitalization of mathematics learning - Pujiastuti, Emi; Rosyida, Isnaini; Sugiman (Al-Jabar: Jurnal Pendidikan Matematika, 2026)
Purpose: This study examines the implementation of digitalized mathematics learning integrated with digital assessment and the Deep Learning approach to support the development of problem-solving competence among Grade X vocational high school students and to evaluate teachers’ readiness to implement the instructional innovation. Method: A convergent parallel mixed-methods design was employed. The study was conducted in five vocational high schools in Central Java, Indonesia. Initial trials were carried out at SVHS 1 Demak and SVHS 1 Pekalongan, followed by field implementation at SVHS Moenadi Ungaran, SVHS 8 Semarang, and SVHS 5 Kendal. Quantitative data were collected through problem-solving competence assessments and teacher performance evaluations, while qualitative data were gathered through interviews, observations, and documentation. Quantitative data were analyzed using descriptive statistics, normality tests, and one-sample t-tests, whereas qualitative data were analyzed through coding, categorization, and thematic interpretation. Findings: Students demonstrated consistently high levels of problem-solving competence across participating schools, with mean scores ranging from 81.44 to 84.94. Teachers also showed strong readiness to develop and implement digitalized mathematics learning, achieving a mean performance score of 86.36, which was significantly higher than the predetermined criterion score. Qualitative findings revealed positive teacher acceptance, active student engagement, and favorable perceptions of the learning experience, although limited internet accessibility remained a practical challenge. Significance: The findings indicate that integrating digitalized mathematics learning, digital assessment, and the principles of Mindful Learning, Meaningful Learning, and Joyful Learning can support problem-solving competence in vocational mathematics education. This study contributes empirical evidence to technology-enhanced mathematics learning and provides practical guidance for implementing student-centered and digitally supported instruction in vocational schools.